Court of Reflections, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
View of the Court of Reflections, with Siamese umbrella lanterns, looking toward the 400-Foot Tower of the Sun at San Francisco's World's Fairs on Treasure Island. Colored lights on walls and gardens produce the after-dark beauty of the courts at this Exposition.